2016
DOI: 10.1007/s10916-016-0591-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Security Competency on “Self-Efficacy in Information Security” for Effective Health Information Security in Iran

Abstract: The security effectiveness based on users' behaviors is becoming a top priority of Health Information System (HIS). In the first step of this study, through the review of previous studies 'Self-efficacy in Information Security' (SEIS) and 'Security Competency' (SCMP) were identified as the important factors to transforming HIS users to the first line of defense in the security. Subsequently, a conceptual model was proposed taking into mentioned factors for HIS security effectiveness. Then, this quantitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…It is believed that nurses currently comply with the HIS recommendations and enforcement rules proposed by medical institutions and that compliance can prevent the leakage of healthcare information. Kajtazi et al [24] also showed that greater self-efficacy related to compliance leads to improved HIS intentions, whereas Shahri et al [11] showed a similar correlation with improved HIS behavior. Our results indicate that it is necessary for interim nurse managers and supervisors to apply achievement-oriented leadership rather than directed leadership [9], thereby exhibiting confidence in nurses who voluntarily perform HIS behavior for its inherent purpose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is believed that nurses currently comply with the HIS recommendations and enforcement rules proposed by medical institutions and that compliance can prevent the leakage of healthcare information. Kajtazi et al [24] also showed that greater self-efficacy related to compliance leads to improved HIS intentions, whereas Shahri et al [11] showed a similar correlation with improved HIS behavior. Our results indicate that it is necessary for interim nurse managers and supervisors to apply achievement-oriented leadership rather than directed leadership [9], thereby exhibiting confidence in nurses who voluntarily perform HIS behavior for its inherent purpose.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, protection motivation was defined as the extent to which nurses are able to cope with losses arising from HIS threats, according to the results of prior studies [5,9,11,12,14,21,[24][25][26][27]31], leading to the following hypothesis: Hypothesis 4 (H4). The coping appraisal of HIS by nurses will affect their behavior.…”
Section: Anticipated Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…The reviewed frameworks [8,[14][15][16]31,38,41,44,45,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] were not fully comprehensive. Meanwhile, security issues are affected by all these aspects and not just psychological, social, cultural, or sociodemographic aspects alone [38].…”
Section: Problem Specification Scope and Contribution Of The Studymentioning
confidence: 99%